2020
DOI: 10.5194/bg-17-5377-2020
|View full text |Cite
|
Sign up to set email alerts
|

Stem and soil nitrous oxide fluxes from rainforest and cacao agroforest on highly weathered soils in the Congo Basin

Abstract: Abstract. Although tree stems act as conduits for greenhouse gases (GHGs) produced in the soil, the magnitudes of tree contributions to total (soil + stem) nitrous oxide (N2O) emissions from tropical rainforests on heavily weathered soils remain unknown. Moreover, soil GHG fluxes are largely understudied in African rainforests, and the effects of land-use change on these gases are identified as an important research gap in the global GHG budget. In this study, we quantified the changes in stem and soil N2O flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The annual soil N 2 O fluxes from the control plots (Table 2) were at the higher end of those measured in (sub-)montane tropical forests (Iddris et al, 2020;Arias-Navarro et al, 2017;Gütlein et al, 2018) and at the lower end of those measured in lowland tropical forest sites (e.g., Koehler et al, 2009b). This may either be due to the differences in soil N cycling rates (Koehler et al, 2009b) or the differences in the spatial abundance of leguminous trees (Xu et al, 2020) at the respective sites.…”
Section: Effect Of N and P Addition And Soil Environmental Controls On Soil N 2 O Fluxesmentioning
confidence: 87%
“…The annual soil N 2 O fluxes from the control plots (Table 2) were at the higher end of those measured in (sub-)montane tropical forests (Iddris et al, 2020;Arias-Navarro et al, 2017;Gütlein et al, 2018) and at the lower end of those measured in lowland tropical forest sites (e.g., Koehler et al, 2009b). This may either be due to the differences in soil N cycling rates (Koehler et al, 2009b) or the differences in the spatial abundance of leguminous trees (Xu et al, 2020) at the respective sites.…”
Section: Effect Of N and P Addition And Soil Environmental Controls On Soil N 2 O Fluxesmentioning
confidence: 87%
“…The annual soil N2O fluxes from the control plots (Table 2) were at the higher end of those measured in (sub-) montane tropical forests (Iddris et al, 2020, Arias-Navarro et al, 2017, Gütlein et al, 2018, and at the lower end of those measured in lowland tropical forest sites (e.g. Koehler et al, 2009b).…”
Section: Effect Of N and P Addition And Soil Environmental Controls Omentioning
confidence: 90%
“…Such patterns have also been reported in other ecosystems: Das et al (2012) and Liang et al (2018) relate daytime N 2 O emission patterns of pastures to changes in soil temperature, while Keane et al (2017) found strong correlation of daytime N 2 O emissions with PAR for oilseed rape. It has also been shown from other environments that N 2 O produced in the soil is taken up by roots, transported into above‐ground plant tissues and finally released into the atmosphere via lenticels or stomata, or N 2 O is consumed along the stem of trees (Iddris et al, 2020; Machacova et al, 2016; Wen et al, 2017). Our analysis in the time‐frequency domain showed that correlations shifted over the course of the day, with variables related to photosynthesis, such as GPP, LE and PAR in , and TKE being associated with N 2 O fluxes at daytime (Figure 8a,c,d,m) and R eco and soil temperature being associated with N 2 O fluxes at night (Figure 8b,k).…”
Section: Discussionmentioning
confidence: 99%